USING ASPEN PLUS TO SIMULATE PHARMACEUTICAL PROCESSES – AN ASPIRIN CASE STUDY - Douglas, Alisa; Elkamel, Ali (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of this paper is to illustrate uses of Aspen Plus (Aspen) to pharmaceutical processes with a specific focus on the production of aspirin. Chemical process simulators such as Aspen have received little attention for pharmaceutical applications; this is due in part to prevalence of dynamic batch reactors, specialized raw materials and products often including solids and solids handling unit operations. Methods: Aspen was used to first validate an experimental study and then extended to a commercial scale process. Results: Aspen adequately reproduced the experimental results obtained from a dynamic batch reactor. Extension to the commercial scale illustrated the power of Aspen to simulate pharmaceutical processes as well as provide costing and economic analysis. Conclusions: It was found that although the modeling of this relatively simple process is more complicated than it initially seemed, Aspen was capable of handling the difficulties inherent in dealing with solids, batch reactions, and crystal growth. In addition, its optimization and economic analysis features provided enhanced flow sheeting functionality. Its batch reactor model, RBATCH, is capable of modeling batch reactors involving multiple solid-liquid reactions following various reaction rate laws.